Macrophages in cardiac development, repair and regeneration - Cahill, T (2018)
Background & Aims Macrophages are highly plastic cells of the innate immune system with a functional repertoire spanning homeostasis, inflammation, repair and remodelling. Originally described as immune cells responsible for phagocytosis and cytokine production, in recent years a plethora of non-classical, tissue-specific, and subspecialised roles for macrophages have emerged. Macrophages have been implicated in organogenesis during embryonic development, and tissue regeneration after injury, often viewed as a recapitulation of development. Understanding the mechanisms underlying these ‘trophic’ functions has translational potential to improve healing in the human heart after myocardial infarction (MI). The principal aim of the work contained in this thesis was to investigate the non-classical roles of macrophages in the heart in the setting of development and following injury, during regenerative and scar-based repair. Methods Macrophage functions were initially investigated during mouse cardiac development. First, the identity, timing, and localisation of macrophages in the embryonic mouse heart was investigated. To gain insight into the functional roles of macrophages in development, heart formation was analysed in a genetic mouse model of macrophage deficiency, the Pu.1-/- mouse. To understand the roles of macrophages in cardiac regeneration, the recently described neonatal mouse model of MI, which heals without scar formation, was compared with the adult mouse which undergoes scarring following injury. Unbiased analysis of the macrophage transcriptome was then conducted by RNA sequencing on isolated macrophages from both regenerative and scar-forming hearts. Putative novel functions for macrophages in injury and repair were then validated. Results Macrophages were found to be present in the embryonic mouse heart from E12.5, and a subset colocalised closely with the developing coronary and lymphatic vasculature. Macrophages did not act as progenitor cells giving rise to the lymphatic vasculature, as has been proposed, although a CSF1R+ myeloid-like progenitor was shown to incorporate into the cardiac lymphatic endothelium. The absence of macrophages in the Pu.1-/- mouse was associated with defects in vessel branching, length and calibre, suggesting that a key role of macrophages in the developing heart is to pattern the coronary and lymphatic vasculature. Following cardiac injury, RNA sequencing demonstrated that macrophages activate distinct transcriptional programmes during tissue healing by regeneration and scar formation. Macrophages were dynamically regulated through the time course of injury and were found to upregulate numerous regenerative and pro-fibrotic soluble factors which modulate tissue repair. Furthermore, in the context of scar formation macrophages expressed extracellular matrix components including collagens, suggesting a direct role in formation of scar. The macrophage response was found to be a key determinant of tissue repair, and adoptive transfer of adult splenic monocytes to the neonatal environment was sufficient to block regeneration, at least in part by direct deposition of collagen. Conclusions Macrophages have previously unrecognised functions in the context of heart development, regeneration and repair. Further analysis of molecular mechanisms, heterogeneity and the intrinsic and environmental factors which regulate macrophage responses is required in order to translate these insights toward therapies for improved repair following human MI.